Bio-removal of rare earth elements from hazardous industrial waste of CFL bulbs by the extremophile red alga Galdieria sulphuraria - Singh, Anjali; Čížková, Mária; Náhlík, Vít; Mezricky, Dana; Schild, Dominik; Rucki, Marian; Vítová, Milada (Frontiers in Microbiology, 2023)
In recent decades, a shift has been seen in the use of light-emitting diodes (LEDs) over incandescent lights and compact fluorescent lamps (CFL), which eventually led to an increase in wastes of electrical equipment (WEE), especially fluorescent lamps (FLs) and CFL light bulbs. These widely used CFL lights, and their wastes are good sources of rare earth elements (REEs), which are desirable in almost every modern technology. Increased demand for REEs and their irregular supply have exerted pressure on us to seek alternative sources that may fulfill this demand in an eco-friendly manner. Bio-removal of wastes containing REEs, and their recycling may be a solution to this problem and could balance environmental and economic benefits. To address this problem, the current study focuses on the use of the extremophilic red alga, Galdieria sulphuraria, for bioaccumulation/removal of REEs from hazardous industrial wastes of CFL bulbs and the physiological response of a synchronized culture of G. sulphuraria. A CFL acid extract significantly affected growth, photosynthetic pigments, quantum yield, and cell cycle progression of this alga. A synchronous culture was able to efficiently accumulate REEs from a CFL acid extract and efficiency was increased by including two phytohormones i.e., 6-Benzylaminopurine (BAP - Cytokinin family) and 1-Naphthaleneacetic acid (NAA - Auxin family).